Search of the route in the network of public communication using a linear sequence method - Keršys, Artūras; Jurkauskas, Algirdas (Transport, 2003)
The problem of searching the route in the network of public communication is being investigated in the article. A new line sequence method working on the base of a real network model is created for route research in transport communication network and the problem solution. Having analysed a modeling peculiarity of passenger behavior choosing the route, the route evaluation and comparison of the resistance function, including the factors for the route chaise are defined: traveling time, cost and comfort (number of changes). On the base of the mathematic calculation results of public transport communication a part model was determined. It offered the method of the work that can be used for the solution of the examined problem and integrated into the prognosis models of communication processes.First Published Online: 19 Dec 2011